2016
DOI: 10.1021/jacs.6b05299
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Design of Photoresponsive Conditional Antivitamins B12: A Transient Absorption Study of an Arylcobalamin and an Alkynylcobalamin

Abstract: Cobalamins are of widespread importance in biology. Both of the cofactors essential for human metabolism, the organocobalamins coenzyme B and methylcobalamin, are highly photolabile, as are other alkylcobalamins. The alkynylcobalamin phenylethynylcobalamin (PhEtyCbl) and the arylcobalamin 4-ethylphenylcobalamin (EtPhCbl) with "atypical" Co-C-bonds to unsaturated carbons, were recently designed as metabolically inert cobalamins, classified as "antivitamins B". The further development of an ideal light-activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
58
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 44 publications
(117 reference statements)
14
58
0
2
Order By: Relevance
“…As reported earlier for ethynyl-Cbl [14] and for 2 , [1112] solutions of 3 were stable to sunlight (SI, Figure S8). In aqueous solution, 3 underwent slow pH-dependent hydrolysis to H 2 OCbl.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…As reported earlier for ethynyl-Cbl [14] and for 2 , [1112] solutions of 3 were stable to sunlight (SI, Figure S8). In aqueous solution, 3 underwent slow pH-dependent hydrolysis to H 2 OCbl.…”
supporting
confidence: 81%
“…Vitamin B 12 (cyanocobalamin, CNCbl) and other cobalamins (Cbls) are indispensable for the mammalian metabolism [1] on account of the essential cofactor activities of coenzyme B 12 (AdoCbl) and methylcobalamin (MeCbl). [2] To provide mammalian cells with AdoCbl and MeCbl, natural Cbls are first transformed into cob(II)alamin (Cbl II )b ythe Cblprocessing chaperone CblC (also named MMACHC,f or methylmalonic aciduria type Ca nd homocystinuria).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, when compared to alkylcobalamins, such as MeCbl , the two isomeric phenyl‐Cbls, PhCbl and αPhCbl , underwent light‐induced interconversion rather slowly. In line with the apparent comparable stability of PhCbl and αPhCbl , recent fsec laser pulse studies with EtPhCbl , indicated this aryl‐Cbl to be far less light‐sensitive than MeCbl and AdoCbl , and to exhibit a low quantum yield of Co−C bond homolysis (<1 %) due to fast internal conversion of the singlet excited state(s) of EtPhCbl to the ground state.…”
Section: Figurementioning
confidence: 84%